Design and Implementation of IoT-Based Smart Home System with ESP8266 for Energy Efficiency - Pancane, I Wayan Dikse; Hermawan, Yudi; Kumara, I Nyoman Indra (Formosa Journal of Computer and Information Science, 2025)
The development of technology for the Internet of Things (IoT) is increasingly sophisticated, enabling humans to control devices with greater ease. This prototype is designed to contribute to the community, particularly in households, by providing convenience and comfort through home automation. The prototype incorporates several features, including the ability to turn lights on and off via a 5V relay. The doors and garages are equipped with MG90S micro servos, facilitating the opening and closing of these structures. The gate is operated by a DC motor, while the clothesline roof cover is designed to automatically adjust based on the external light conditions, opening and closing in response to changes in brightness. The operation of these systems is managed through the Blink application, which utilizes an Android mobile phone as the control interface